A note on seasonal breaks in tourism demand time series. (July 2014) - Gouveia, Pedro MDCB
In this paper, a structural break test procedure proposed in literature is employed in a tourism demand analysis context. This article is the first to apply a graphical approach using seasonal surface and seasonal contour maps, which can be important tools for seasonal pattern evolution analyses. For the purpose of empirical study, total lodging figures were selected to analyze British tourism demand in the Algarve. The seasonality of tourism demand has several effects on economic activity. Identifying seasonal breaks in tourism time series allowed us to obtain evidence of efforts to lessen seasonality and that can hopefully benefit long-run policy evaluation and planning.